DEVELOPING BACTERIOPHAGE-BASED ASSAYS FOR THE RAPID DETECTION OF MYCOBACTERIA - Handley-Hartill, Wade (2023)
Mycobacteria are a genus of bacteria that are very specialized and are the causative agents of many significant diseases across multi sectors and in a very wide range of species. Detection of these organisms can be difficult due to the slow growing nature of the majority of the pathogenic mycobacteria in vitro. The very close similarity between these organisms also causes cross reactions with many assay designed to detect a specific mycobacterial species. The aim of these studies was to develop bacteriophage-based assay for the rapid detection of mycobacteria. PCR assays were designed to improve the detection of paucibacillary samples including a novel control strain of M. smegmatis. The novel strain could be used as a phage infection control for both the standard phage assay and the Oneday phage assay, a rapid mycobacterial detection method. By using bacteriophage-based assays we identified in these studies MTBC bacteraemia of human patients during early LTBI stage. We also identified two separate cases of LTBI reverting to active disease months before clinical symptoms were produced by the patients. MAP was also detected during the same double blind trial unexpectedly in a human patient with sarcoidosis. The result was produced after plaques were produced on the standard phage assay from the blood of this patient which were shown to be MTBC negative. Further PCR analysis identified the plaques as deriving from S-Type MAP. S-Type MAP was also shown to cause a cross reaction with the tuberculin skin test in bison which were mistakenly sent to slaughter due to the false positive TST results.